Preventing recurrent acute otitis media with Streptococcus salivarius 24SMB and Streptococcus oralis 89a five months intermittent treatment: An observational prospective cohort study. (May 2020) - Cantarutti, Anna; Rea, Federico; Donà, Daniele; Cantarutti, Luigi; Passarella, Andrea; Scamarcia, Antonio; Lundin, Rebecca; Damiani, Valerio; Giaquinto, Carlo; Corrao, Giovanni
Abstract: Introduction: Acute otitis media (AOM) is the most common childhood disease leading to antibiotic use. More than 80% of children under three years of age experience at least one episode, and about one-third of these report significant recurrence of episodes. In recent years, several studies reported that normal nasopharyngeal flora inhibits growth of common otopathogens, suggesting that maintenance of an "adequate" nasopharyngeal flora might prevent occurrence of upper respiratory tract infections, including AOM. This study aims to determine whether five-month treatment with Streptococcus salivarius 24SMB and Streptococcus oralis 89a nasal spray prevents recurrence of AOM and prescription of antibiotics in children with diagnosis of recurrent AOM. Methods: Observational prospective cohort study including children aged 1–6 years with diagnosis of recurrent AOM registered with 31 Italian family pediatricians. 81 children were enrolled in the study from September 2016 to the end of the five therapeutic cycles of the Streptococcus salivarius 24SMB and Streptococcus oralis 89a supplied 7 days each month for 5 consecutive months. For each treated child, one untreated control was randomly selected, 1:1 matched for gender, age, and follow-up. Results: 158 children (79 treated and 70 untreated) were included into the analysis (mean age, 3.9 years; 47% female). Univariate analysis showed a statistically significant 34% (95% CI 1%–56%) reduction in number of AOM episodes in treated children compared with those not treated. Significantly fewer antibiotics were dispensed among treated children (24%, 95% CI 1%–41%). Conclusions: Our findings suggest that intermittent treatment of children with diagnosis of recurrent AOM with nasal spray containing Streptococcus salivarius 24SMB and Streptococcus oralis 89a for a period of five months might be effective in preventing antibiotic use associated with recurrent episodes of AOM. Additional larger studies to address this important clinical problem are recommended.